2D Antimony–Arsenic Alloys. Issue 3 (26th December 2019) - Fortin‐Deschênes, Matthieu; Waller, Olga; An, Qi; Lagos, Maureen J.; Botton, Gianluigi A.; Guo, Hong; Moutanabbir, Oussama
Abstract: Alloying in group V 2D materials and heterostructures is an effective degree of freedom to tailor and enhance their physical properties. Up to date, black arsenic‐phosphorus is the only 2D group V alloy that has been experimentally achieved by exfoliation, leaving all other possible alloys in the realm of theoretical predictions. Herein, the existence of an additional alloy consisting of 2D antimony arsenide (2D‐As x Sb1− x ) grown by molecular beam epitaxy on group IV semiconductor substrates and graphene is demonstrated. The atomic mixing of As and Sb in the lattice of the grown 2D layers is confirmed by low‐energy electron diffraction, Raman spectroscopy, and X‐ray photoelectron spectroscopy. The As content in 2D‐As x Sb1− x is shown to depend linearly on the As4 /Sb4 deposition rate ratio and As concentrations up to 15 at% are reached. The grown 2D alloys are found to be stable in ambient conditions in a timescale of weeks but to oxidize after longer exposure to air. This study lays the groundwork for a better control of the growth and alloying of group V 2D materials, which is critical to study their basic physical properties and integrate them in novel applications. Abstract : This work shows the first experimental demonstration of the growth of 2D arsenic–antimony alloys. The growth is achieved by solid‐source molecular beam epitaxy. This novel family of group V 2D alloys presents a rich playground to achieve highly tunable properties for integration in scalable nanoscale and quantum technologies.